P771 Biologics versus azathioprine in steroid-dependent ulcerative colitis: results from the A.U.R.O.R.A. database. (30th January 2023) - Cassinotti, A; Saibeni, S; De Silvestri, A; Mezzina, N; Di Paolo, D; Alimenti, E; Annunziata, M L; Albertini Petroni, G; Segato, S; Canova, L; Italia, A; Zammarchi, I; et al.
Abstract: Background: The A.U.R.O.R.A. database is an Italian multicenter retrospective cohort of patients with ulcerative colitis (UC) treated with the first biological drugs (infliximab biosimilar- IFX-B, adalimumab-ADA, golimumab-GOL, vedolizumab-VDZ) approved in Italy after patent expire of IFX-originator. In a previous published study, 1 we showed similar efficacy among all drugs according to the rigorous outcome of 1-year "continuous clinical remission" (CCR). In this study, we focused only on steroid-dependent UC, by comparing all drugs to each other and to patients treated with steroids followed by azatioprine (AZA) monotherapy. Methods: All consecutive patients with steroid-dependent UC, treated with IFX-B, ADA, GOL or VDZ after their approval in 2014-2019, were followed-up for 1 year or until drug discontinuation for relapse or adverse events. All drugs were compared to each other and to steroid-dependent patients treated with steroids + AZA in 2006-2014. A propensity score analysis was performed to balance differences at baseline. The primary endpoint was the 1-year CCR, defined as steroid-free clinical remission with Mayo partial score ≤2 (with no bleeding), without any clinical relapse or treatment optimization after the first remission was achieved, and without drug withdrawal due to adverse events. Treatment optimization was defined as the addition of systemic/topical steroids, oral/topical mesalazine or any dose escalation of biologics Results: 370 patients (IFX-B=62, ADA=68, GOL=56, VDZ=100, AZA 84) with steroid-dependent UC were included. No significant differences were found among each biological drug according to the 1-year CCR primary end-point (34%, 29%, 30%, 39%, respectively). In patients naive to immunesuppressors and biologics (n= 17, 25, 24 10, 79, respectively), AZA showed significantly higher rate of CCR (68%) than each biological drug (35%, 44%, 33%, 60%; p =0.000 for each comparison) or all biologics as a whole (41%; p =0.012). Adverse events occurred significantly less frequently with ADA (8%) than IFX (29%), GOL (20%) and AZA (26%) in the overall population, but were similar across all drugs in the naive population. Discontinuation for adverse events occurred more frequently ( p <0.05) with both IFX-B (16%) and AZA (14%) than ADA (3%), GOL (4%), and VDZ (1%) in the overall population, but not in the naive population (18%, 15%, 4%, 4%, 0%, respectively). Conclusion: In steroid-dependent UC, anti-TNF-alpha agents and VDZ were equally effective at 1 year according to the concept of CCR. AZA still appears an effective first-line strategy in the biological era. 1 Cassinotti A. et al. Eur J Gastroenterol Hepatol. 2022;34:1238-46. Guided Poster Session